Talent Management and Organizational Performance: A Study in South-West Nigeria - Epebinu, Olufemi; Oguntuase, Dolapo; Oruma, Alhassan (Business Perspective Review, 2024)
Purpose: This study was carried out to examine the empirical effect of talent management on organizational performance in two selected wire and cable firms operating in South-West Nigeria. Method: A questionnaire was used as a research instrument to source data from a population of 186 employees from the two selected firms. Multi-stage sampling procedure was deplored to arrive at a sample size of 127. Data were analyzed using both descriptive and inferential statistics using Statistical Package for Social Sciences (SPSS) version 20. Result: The study revealed that talent management has a significant positive effect on Organizational Performance. [Model R-square =.623 and P ˂ 0.05]. It indicates a predictive power of the outcome in the model as approximately 62% of variation in Organizational Performance is explained by talent management practices. Implication: The result implies that the firms should pay more attention to the selected talent management practices (talent attraction, talent retention, learning and development, and career management) in order to ensure a higher level of organizational performance.